Blended learning in the development of university students’ metacognition - Malik, Umit; Malikov, Anuar; Abdyhalykova, Zhazira (Institute of Advanced Engineering and Science, 2024)
In the conditions of the advancing digitalization and the introduction of restrictions aimed at combating the COVID-19 pandemic, there is a search for new formats of learning at universities, the most promising of which the authors believe to be blended learning. The study aims to assess the effectiveness of the development of metacognition in a university blended learning environment. The development of students’ metacognition as part of an empirical study is achieved by a set of methods, the key among which is the experiment. The results of the experimental study suggest that students’ perception of the environment of blended learning tends to improve. In particular, improvement is observed in the indicators of some metacognitive skills (the choice of the place and time of training, planning of learning activities, monitoring of the obtained knowledge, and the experience of working with information). The results reveal improvements in the self-regulatory component of metacognition. As a result of the study, it is concluded that the comprehensive development of metacognitive skills among students ensures their engagement in learning and greater consciousness and proves useful in the context of blended learning.